Investment Analysis of Establishment the Architectural Technical Design Service as a Creative Economy Based on BMC (Case Study in East Java Province) - Insan Marthian; Bambang Syairudin (Institut Teknologi Sepuluh Nopember, 2019)
National GDP and East Java Province GRDP show an increasing trend. The increase occurred because it was supported by an increase in several macro-industries such as the creative industry, real estate industry, and others. This shows good economic conditions in East Java Province. While the increase in the number of new households continues to increase, the need for home ownership continues to increase and the backlog of homes in East Java is still high above around 1,000,000 housing units every year, so the need for architectural services to make the design of houses or buildings still exists. Therefore, further analysis is needed by analyzing the investment feasibility study in establishing an architectural design service business. Investment analysis is done by making the business model based on BMC and analyzing from several aspects such as financial aspects and non-financial aspects (market and marketing aspects, operational aspects, and management aspects). This study uses qualitative methods, where data collection is done by means of discussion (Focus Group Discussion), interviews, and through literature. By conducting an investment feasibility study based on the BMC business model, it is expected to obtain a feasible business model for Architectural services business in meeting the needs of the design of the house or building